CHESS 3: an improved, comprehensive catalog of human genes and transcripts based on large-scale expression data, phylogenetic analysis, and protein structure - Varabyou, Ales; Sommer, Markus J.; Erdogdu, Beril; Shinder, Ida; Minkin, Ilia; Chao, Kuan-Hao; Park, Sukhwan; Heinz, Jakob; Pockrandt, Christopher; Shumate, Alaina; Rincon, Natalia; Puiu, Daniela; et al. (Genome Biology, 2023)
CHESS 3 represents an improved human gene catalog based on nearly 10,000 RNA-seq experiments across 54 body sites. It significantly improves current genome annotation by integrating the latest reference data and algorithms, machine learning techniques for noise filtering, and new protein structure prediction methods. CHESS 3 contains 41,356 genes, including 19,839 protein-coding genes and 158,377 transcripts, with 14,863 protein-coding transcripts not in other catalogs. It includes all MANE transcripts and at least one transcript for most RefSeq and GENCODE genes. On the CHM13 human genome, the CHESS 3 catalog contains an additional 129 protein-coding genes. CHESS 3 is available at http://ccb.jhu.edu/chess .